2011
DOI: 10.1093/fampra/cmr023
|View full text |Cite
|
Sign up to set email alerts
|

Pre-arrest predictors of failure to survive after in-hospital cardiopulmonary resuscitation: a meta-analysis

Abstract: We identified several pre-arrest variables associated with failure to survive to discharge. This information should be shared with patients as part of a shared decision-making process regarding the use of do not resuscitate orders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
131
2
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(156 citation statements)
references
References 52 publications
7
131
2
7
Order By: Relevance
“…Several investigations have reported low hospital discharge survival aft er CPR in patients with malignancy. [26][27][28] A 2006 meta-analysis of 1,707 patients with cancer found that 6.2% of all CPR recipients with malignancy and 5.6% of those with metastases survived to hospital discharge, 26 whereas we found that 12.3% of all patients with malignancy and 11.7% of patients with severe malignancy survived to hospital discharge. A possible explanation for these confl icting results is differing study populations.…”
Section: Discussioncontrasting
confidence: 52%
“…Several investigations have reported low hospital discharge survival aft er CPR in patients with malignancy. [26][27][28] A 2006 meta-analysis of 1,707 patients with cancer found that 6.2% of all CPR recipients with malignancy and 5.6% of those with metastases survived to hospital discharge, 26 whereas we found that 12.3% of all patients with malignancy and 11.7% of patients with severe malignancy survived to hospital discharge. A possible explanation for these confl icting results is differing study populations.…”
Section: Discussioncontrasting
confidence: 52%
“…2,4,7,10,11 Furthermore, patients who were successfully resuscitated often undergo aggressive treatment in the intensive care unit and suffer complications including rib fractures, permanent neurological deficits, and impaired functional status. 4,12,13 Even without physical injury, CPR can lead to psychological harm that lowers survivors' quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…A primary diagnosis of acute myocardial infarction has been associated with increased survival rate to discharge [19], whereas the presence of cancer, metastatic disease, sepsis or pneumonia has been associated with poor outcome. Our patients were reported to have suffered from cardiac arrest in the majority of the cases, a higher proportion than that reported in the literature [25], yet only 30% suffered from acute myocardial infarction indicating that the labeling of cardiac arrest is probably overestimated or that it was a mixed respiratory cardiac arrest.…”
Section: Discussionmentioning
confidence: 99%
“…In addition use of mechanical ventilation, vasopressors in critically ill patients are indicators of low likelihood of survival following arrests [13] [17] [18]. On the other hand, acute myocardial infarction and the presence of shockable rhythms such as ventricular tachycardia (VT) or ventricular fibrillation (VF) have been associated with good outcome [19], four to five times higher than patient with asystole or pulseless electrical activity (PEA).…”
mentioning
confidence: 99%